Ґенеза економічної інтеграції України до ЄС - Посохов, Ігор Михайлович; Сусліков, Станіслав Вячеславович; Гусарова, Дар'я Михайлівна (ТОВ "Міжнародний бізнес центр", 2024)
У статті розглянуто ґенезу економічної інтеграції України до ЄС. Проаналізовано виконання Угоди про асоціацію за 2022 та 2023 рр., а також сильні та слабкі сторони очікуваних можливостей та загроз інтеграції України до ЄС. Напрямом подальших наукових досліджень вважаємо за необхідне розглянути саме митні та податкові аспекти економічної інтеграції України, оскільки завдяки саме податковим та митним платежам забезпечується формування доходноїчастини бюджету з подальшим її перерозподілом на різні соціально-економічні цілі держави.

The paper examines the genesis of economic integration of Ukraine to the EU. The purpose of the paper is to investigate the genesis of economic integration of Ukraine to the EUand develop recommendations for their development. The result of bilateral trade integration following the implementation of the consolidated and all-inclusive free trade zone was the modernization of Ukraine's trade policy. The primary dominants may include: the increase in trade turnover between the countries and the increase in the share of European countries in the structure of foreign trade of Ukraine; changes in import duties; improved access to the market; harmonization of legislation; establishment of tariff quotas; а further reduction in non-tariff barriers to trade; home ownership of the region is one hundred percent improved robotic work; harmonization of the technical regulation system; systems of standardization, metrology, conformity assessment and market visibility; sanitary and phytosanitary visits; Strengthening the protection of intellectual rights. The genesis of economic integration of Ukraine to the EU was investigated. An analysis of the Vikonanny Ugodi about association for 2022 and 2023 was carried out. We have analyzed the strengths and weaknesses, the emerging opportunities and threats to the integration of Ukraine into the EU. Directly from further scientific research, it is important to look at the most important aspects of the economic integration of Ukraine, since the most important payments will ensure the formation of the revenue side of the budget from further It is re-divided into different socio-economic goals of the state.
Genesis of economic integration of Ukraine into the EU
Keywords: внутрішній ринок ЄС; інтеграція України до ЄС; економічна інтеграція; секторальна інтеграція; ЄС; тарифна лібералізація; угода про асоціацію; internal market of the EU; integration of Ukraine to the EU; economic integration; sectoral integration; EU; tariff liberalization; benefit of association